Roses and Balances: A Paradigm for Constructive Ethical Review of Health Professions Education Research - Schutte T; Scheele F; van Luijk S (Advances in Medical Education and Practice, 2021)
Tim Schutte,1,2 Fedde Scheele,3,4 Scheltus van Luijk5 1Department of Internal Medicine, Amsterdam UMC, Amsterdam, The Netherlands; 2Department of Internal Medicine, Zaans Medisch Centrum, Zaandam, The Netherlands; 3Athena Institute for Transdisciplinary Research, VU University, Amsterdam, The Netherlands; 4Department of Healthcare Education, OLVG Hospital, Amsterdam, The Netherlands; 5Institute for Post Graduate Education MUMC+, Medical University Hospital, Maastricht, The NetherlandsCorrespondence: Tim Schutte Email t.schutte@amsterdamumc.nlAbstract: Recently, the balance between value and necessity of ethical review of health professions education research has been debated. At present, there are large differences in how ethical review of research proposals for health professions education is organized. We present a framework that describes the organization of ethical review in health professions education research, based on the interpersonal circumplex model, also known as Leary’s Rose. The framework is based on the two main balances in ethical review of health professions education research, being the protectiveness for the subjects and how ethical review is organized and responsibilities are shared. The axis/balance of protectiveness ranges between the extremes “paternalistic protective” to “liberal permissive”. The axis/balance of organization and responsibility ranges between the extremes of “centralized” to “local/decentralized”. This model offers insight in the position of an ethical review board and shows the dynamics of the decisions for ethical approval and the consequences of the different approaches to the organization of ethical review of health professions education research.Keywords: ethical review, health professions education research, ethical approval of health professions education research